2015
DOI: 10.1063/1.4929420
|View full text |Cite
|
Sign up to set email alerts
|

Coupled ion redistribution and electronic breakdown in low-alkali boroaluminosilicate glass

Abstract: Dielectrics with high electrostatic energy storage must have exceptionally high dielectric breakdown strength at elevated temperatures. Another important consideration in designing a high performance dielectric is understanding the thickness and temperature dependence of breakdown strengths. Here, we develop a numerical model which assumes a coupled ionic redistribution and electronic breakdown is applied to predict the breakdown strength of low-alkali glass. The ionic charge transport of three likely charge c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Previous experimental and theoretical modeling studies have shown similar trends in the temperature‐dependent breakdown strength up to 150°C and Fig. shows a continuing trend up to temperatures of 400°C . The primary breakdown mechanism involves the formation of a high electric field region that is created by the depletion of mobile sodium ions .…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Previous experimental and theoretical modeling studies have shown similar trends in the temperature‐dependent breakdown strength up to 150°C and Fig. shows a continuing trend up to temperatures of 400°C . The primary breakdown mechanism involves the formation of a high electric field region that is created by the depletion of mobile sodium ions .…”
Section: Resultssupporting
confidence: 53%
“…2 shows a continuing trend up to temperatures of 400°C. 14 The primary breakdown mechanism involves the formation of a high electric field region that is created by the depletion of mobile sodium ions. 15 The increased mobility of the sodium ion coupled to thermally activated electron transport contributes to thickness and temperature-dependent break down.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation